Pengembangan Sistem Informasi Jadwal Penerimaan Barang Masuk Logistik Pada PT. Food Beverages Indonesia Dengan Metode Waterfall - Suhardi Suhardi (DPPM Universitas Pelita Bangsa, 2022)
Warehousing is part of a company's logistics system which has the main activity of receiving, storing and shipping goods. The information system applied to warehousing at PT. Food Beverages Indonesia still has shortcomings, including the lack of information regarding the schedule for receiving incoming goods from a more specific local area. Then the problem of information regarding the unloading process that is not in accordance with the existing provisions in the warehouse so that this lack of information causes the service to be delayed, both warehouse operators and related parties in the warehousing department. In this final project, a system analysis is carried out to design a web application for receiving information systems. With the application of a web-based system, it is hoped that it can overcome the problems that exist in the company in the warehousing section, because through this new system information can be accessed directly from anywhere as long as there is internet. Warehouse reporting is also directly integrated from existing data so that it can manage data quickly, precisely and accurately. This application can be used by PT. Food Beverges Indonesia, especially the reception staff, takes an inventory of the products in the warehouse. Inventory includes recording, processing and reporting of data in the warehouse. The application is built using the waterfall model process method, PHP programming language, MySQL database. The design of the warehousing information system produces inputs and outputs that support the performance of the warehouse. Keywords: logistics, schedule, acceptance, information system, PHP, MySQL, Waterfall.